2013
DOI: 10.1016/j.cell.2012.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Control of Nutrient Stress-Induced Metabolic Reprogramming by PKCζ in Tumorigenesis

Abstract: SUMMARY Tumor cells have high-energetic and anabolic needs and are known to adapt their metabolism to be able to survive and keep proliferating under conditions of nutrient stress. We show that PKCζ deficiency promotes the plasticity necessary for cancer cells to reprogram their metabolism to utilize glutamine through the serine biosynthetic pathway in the absence of glucose. PKCζ represses the expression of two key enzymes of the pathway, PHGDH and PSAT1, and phosphorylates PHGDH at key residues to inhibit it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
178
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 166 publications
(192 citation statements)
references
References 33 publications
6
178
0
Order By: Relevance
“…In this regard, the work of Sun and co-workers show that when cancer cells are deprived of glucose or glutamine, the serine biosynthesis pathway (SSP) is activated [3] (Figure 1). These results confirm previous data in colon cancer cells demonstrating that glucose deprivation promotes cell death unless they are deficient in the atypical PKC, PKCζ, and thus they can synthesize serine and glycine from glutamine through a process of "reverse glycolysis" [4]. Interestingly, Sun et al [3] extended these observations and made the important finding that the SSP pathway is activated not only under glucose deprivation condition [4] but also when cells are deprived of glutamine.…”
supporting
confidence: 78%
“…In this regard, the work of Sun and co-workers show that when cancer cells are deprived of glucose or glutamine, the serine biosynthesis pathway (SSP) is activated [3] (Figure 1). These results confirm previous data in colon cancer cells demonstrating that glucose deprivation promotes cell death unless they are deficient in the atypical PKC, PKCζ, and thus they can synthesize serine and glycine from glutamine through a process of "reverse glycolysis" [4]. Interestingly, Sun et al [3] extended these observations and made the important finding that the SSP pathway is activated not only under glucose deprivation condition [4] but also when cells are deprived of glutamine.…”
supporting
confidence: 78%
“…Previous study by Ma et al [30] demonstrated that glucose deprivation allows not only the nitrogen, but also the carbon of glutamine to be incorporated into serine. Here our results also indicated that cMyc is critically involved in the regulation of SSP ( Figure 2F and Supplementary information, Figure S1), hence coordinating metabolism of glucose, glutamine and serine/glycine for cell survival and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported recently that, upon serine starvation, p53 activates p21 to promote GSH production to combat ROS [25,26]. Additionally, p73, ATF4, G9A, HIF1 and PKCζ were also reported to regulate serine biosynthesis and metabolism [27][28][29][30][31]. However, compared to the profound understanding of glycolysis and glutaminolysis in cancer cells, we are only beginning to appreciate the critical impact of serine synthesis pathway (SSP) on cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…PKCζ represses the expression of either PHGDH and PSAT1 enzymes, diminishing or abolishing the flux of 3-phospoglycerate to serine formation, and it could be the reason of why PKCζ acts as a tumor suppressor. These findings suggest that malignant cells exhibit metabolic flexibility to sustain growth and survival [94].…”
Section: Energy Addiction Growth and Proliferationmentioning
confidence: 95%
“…However, AMPK activation under nutrient deprivation or in tumor cell lines genetically programmed by oncogenes can maintain Tumor Biol. metabolic homeostasis and survive [93,94]. It explains in part the interplay between glutamine metabolism and AMPK, despite the fact that the full mechanism is not currently understood.…”
Section: Energy Addiction Growth and Proliferationmentioning
confidence: 99%